HepCCATT: a multilevel intervention for hepatitis C among vulnerable populations in Chicago. (22nd June 2021) - Tilmon, Sandra; Aronsohn, A; Boodram, B; Canary, L; Goel, S; Hamlish, T; Kemble, S; Lauderdale, D S; Layden, J; Lee, K; Millman, A J; Nelson, N; et al.
Abstract: Background: Hepatitis C infection could be eliminated. Underdiagnosis and lack of treatment are the barriers to cure, especially for vulnerable populations (i.e. unable to pay for health care). Methods: A multilevel intervention from September 2014 to September 2019 focused on the providers and organizations in 'the safety net' (providing health care to populations unable to pay), including: (i) public education, (ii) training for primary care providers (PCPs) and case managers, (iii) case management for high-risk populations, (iv) policy advice and (v) a registry (Registry) for 13 health centers contributing data. The project tracked the number of PCPs trained and, among Registry sites, the number of people screened, engaged in care (i.e. clinical follow-up after diagnosis), treated and/or cured. Results: In Chicago, 215 prescribing PCPs and 56 other health professionals, 86% of whom work in the safety net, were trained to manage hepatitis C. Among Registry sites, there was a 137% increase in antibody screening and a 32% increase in current hepatitis C diagnoses. Engagement in care rose by 18%. Conclusions: Hepatitis C Community Alliance to Test and Treat (HepCCATT) successfully targeted safety net providers and organizations with a comprehensive care approach. While there were challenges, HepCCATT observed increased hepatitis C screening, diagnosis and engagement in care in the Chicago community.